Developing a Social Media Marketing Plan for CITY89 Brand of BiCi Center Company Limited - Huynh, Thi Tuyet Trinh (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.